THE COMPLETE PATHOMORPHOLOGICAL RESPONSE TO NEOADJUVANT THERAPY AND ITS ROLE IN THE TREATMENT STRATEGY FOR RECTAL CANCER - A. M. Karachun (Тазовая хирургия и онкология, 2015)
The therapeutic strategy in rectal cancer has substantially changed in the past decade. Total mesorectumectomy has been widely used. Many specialized health facilities have accepted radio/chemoradiotherapy for locally advanced rectal cancer as a standard. At the same time as high as one quarter of the patients receiving neoadjuvant therapy demonstrate a complete pathomorphological regression of a tumor. In this connection, the current literature discusses whether medical treatment is permissible in this group of patients.